Legal and Ethical Implications of Absentee Ownership in Agricultural Land Transactions: The Position of the Land Deed Official - Ester Imanuela Dwi Putri; Moh Fadli; Supriyadi (Institut Agama Islam Negeri Curup, 2025)
This study aims to analyze the legal consequences of a sale and purchase deed of absentee agricultural land made by a Land Deed Official. The issue being studied is the drafting of a sale and purchase deed by a Land Deed Official for absentee agricultural land, where the ownership of such land has been prohibited as stipulated in Article 3d of Government Regulation Number 41 of 1964 concerning Amendments and Additions to Government Regulation Number 224 of 1961 on the Implementation of Land Redistribution and Compensation. Furthermore, the Land Deed Official is obliged to refuse to draft deeds that contradict the prevailing laws and regulations, particularly in relation to absentee agricultural land, as regulated in Article 39 paragraph (1) letter g of Government Regulation Number 24 of 1997 concerning Land Registration. This research employs normative juridical research using the statutory approach, conceptual approach, case approach, and historical approach. The legal materials used in this research consist of primary legal materials and secondary legal materials. The research findings indicate that the legal consequences of a sale and purchase deed drafted by a Land Deed Official for absentee agricultural land are in conflict with the prevailing laws and regulations, specifically Article 1320 of the Indonesian Civil Code (KUHPer) concerning the validity requirements of an agreement, as it violates both subjective and objective requirements. As a result, the sale and purchase deed becomes null and void by operation of law, rendering it invalid or deemed never to have existed.